2013
DOI: 10.1097/aln.0000000000000017
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin Rectifies Aberrant Brain Chemistry, Connectivity, and Functional Response in Chronic Pain Patients

Abstract: The results of this study suggest that pregabalin works in part by reducing insular glutamatergic activity, leading to a reduction of the increased functional connectivity seen between brain regions in chronic pain states. The study also supports a role for human brain imaging in the development, assessment, and personalized use of central-acting analgesics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
216
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 233 publications
(240 citation statements)
references
References 44 publications
20
216
4
Order By: Relevance
“…We have shown that gabapentin blocks ICS-induced fibromyalgia-like pain via supraspinal mechanisms, whereas it inhibits nerve injury-induced neuropathic pain via spinal mechanisms (Nishiyori and Ueda, 2008). Consistently, a recent clinical neuroimaging study has shown that pregabalin inhibits neuronal connectivity in the brain regions of fibromyalgia patients (Harris et al, 2013). Therefore, neuropathic pain and fibromyalgia-like pain may show the difference in the site of donepezil actions, possibly owing to their distinct molecular basis.…”
Section: Discussionsupporting
confidence: 48%
“…We have shown that gabapentin blocks ICS-induced fibromyalgia-like pain via supraspinal mechanisms, whereas it inhibits nerve injury-induced neuropathic pain via spinal mechanisms (Nishiyori and Ueda, 2008). Consistently, a recent clinical neuroimaging study has shown that pregabalin inhibits neuronal connectivity in the brain regions of fibromyalgia patients (Harris et al, 2013). Therefore, neuropathic pain and fibromyalgia-like pain may show the difference in the site of donepezil actions, possibly owing to their distinct molecular basis.…”
Section: Discussionsupporting
confidence: 48%
“…PGB is believed to reduce the magnitude of the enhanced pronociception process in FMS (Crofford et al, 2005;Arnold et al, 2008;Mease et al, 2008). Imaging studies using fMRI confirmed that PGB connects neuronal connectivity and biochemical aspects of pain in FMS (Harris et al, 2013;Kim et al, 2013).…”
Section: Treatmentmentioning
confidence: 94%
“…For instance, it has been shown that pain reduction induced by pregabalin intake was related to a decrease in connectivity between the default mode network (DMN) and the insular cortex [59], which is hyperactivated in patients with chronic pain [60,61]. In another neuroimaging study (i.e., functional MRI) evaluating the effects of M1 tDCS in patients with fibromyalgia, the authors demonstrated that tDCS induced a significant reduction in functional connectivity between the thalamus and the supplementary motor area, the medial prefrontal cortex and the cerebellum [62].…”
Section: How To Improve the Effects Of Tdcs?mentioning
confidence: 99%